RELIEF TOKOH BERJENGGOT PADA CANDI-CANDI DI JAWA TENGAH (KAJIAN MAKNA PENEMPATAN DAN PERAN) - , ANGLIR BAWONO; , Dra. Niken Wirasanti, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research discusses a pair of bearded figure in Central Javanese temple. This research also tries to identify these figures which were depicted on the Central Javanese reliefs. Moreover the research aims to to reveal the role and meaning of the position of these figures. Temple was replica of Mount Meru which was perceived as the place of gods in Indian mythology. As a place of gods, temple was also built in order to imitate the celestial world. Thus, temple had components depicting the celestial world as the place of gods. These components are represented by kalpavá¹ksa, gods who inhabited the celestial world, and other creatures. On the temple, the visualization of celestial milieu could be represented in statue or reliefs. One of the celestial world inhabitants was parivÄradevatÄ. ParivÄradevatÄ was one of icons who was not placed in the main chamber of the temple, but surround of temple corridor. Several parivÄradevatÄ figures had been already identified. However, amongst of them were still not yet known including the bearded figures. These bearded figures had been found in some Central Javanese temples. The representation of these figures as statue on temple are often regarded as Agastya, particularly in Hindu Javanese temple. On the other hand, the representation of these figures on the templeâs reliefs is perceived as á¹á¹£i. Nevertheless, the representation of these figures on the both side of other figures or which appears on temple doorstep has not been known yet. As a matter of fact the representation of these figures on the temple is of course having particular meaning related with temple cosmology. Based on this problem, a research about a pair of bearded figures is undoubtedly needed. Furthermore, the ultimate position of these figures on the doorstep of temple or on the both side of another figure convincingly demonstrates its particular role. The research method used in this research is descriptive-analytical in which on the beginning of this research is aimed to describe the representation of bearded figures in temple and its position. On the subsequent stage, these figures are analyzed through scientific approach. The method to analyze these figures is iconography in order to reveal this pair of bearded figure. Key words: pair of bearded figure, reliefs, parivÄradevatÄ, Indian mythology, iconography